Electrochemical behavior of Zn‐REP nanohybrid coatings during marine Shewanella sp. biofilm formation - Galicia, Monica (2021)
Nanohybrid coatings, particularly zinc‐rich epoxy coatings, can protect steel from the harsh marine environment through a physical barrier mechanism and a cathodic protective effect based on anodic electrochemical reactions involving zinc particles in the coating. New additives, such as carbon nanotubes (CNTs), produce more efficient multifunctional coatings by enhancing both protective mechanisms. In this study, the electrochemical behavior and corrosion mechanisms of zinc‐rich epoxy nanohybrid coatings with the addition of CNTs were investigated in the presence of a Shewanella sp. marine strain to evaluate their influence on biofilm formation by this Gram‐negative bacterium. The electrochemical activity was monitored over time with opencircuit potential, electrochemical impedance spectroscopy, and scanning electron microscopy coupled with energy‐dispersive X‐ray spectroscopy. A mixed mechanism was observed starting from early exposure. When the content of CNTs was doubled, the biofilm adherence improved, thus suggesting a favorable effect of CNTs on biofilm formation, attributable to increased production of bacterial exopolymeric substances facilitating biofilm development. The electrochemical impedance spectroscopy results suggested a correlation with biofilm formation as a second barrier layer with the lowest impedance magnitude in coatings with different multiwalled CNT content.